2017
DOI: 10.1002/jum.14446
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Fetal Growth Disorders Using Ultrasonography in Women With Diabetes

Abstract: Ultrasonography in women with diabetes and term or late preterm pregnancies has high specificity but poor sensitivity for SGA and a low positive predictive value for LGA. The diagnostic capability of US to detect fetal growth abnormalities did not differ significantly by the type of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Transabdominal ultrasound was performed to determine fetal weight. If the estimated weight was under the 10 th percentile according to the Hadlock formula [16], Doppler ultrasound of the UA and MCA was done. Ultrasound examination was carried out by an expert perinatologist (who was blinded to the study) using Doppler and high resolution ultrasonography (ACUSON Sequoia 512 TM , Siemens Healthcare GmbH, made in USA).…”
Section: (A) Study Population and Study Designmentioning
confidence: 99%
“…Transabdominal ultrasound was performed to determine fetal weight. If the estimated weight was under the 10 th percentile according to the Hadlock formula [16], Doppler ultrasound of the UA and MCA was done. Ultrasound examination was carried out by an expert perinatologist (who was blinded to the study) using Doppler and high resolution ultrasonography (ACUSON Sequoia 512 TM , Siemens Healthcare GmbH, made in USA).…”
Section: (A) Study Population and Study Designmentioning
confidence: 99%
“…Dude and Yee comment that the sensitivity of ultrasound to detect SGA in pregnancies complicated by diabetes is considerably worse than pregnancies without diabetes and that as clinicians likely have a higher index of suspicion for macrosomia, rather than growth restriction in this population, a substantial number of SGA infants may be missed. 25 At the higher end of the growth spectrum, the most common marker of LGA is an EFW >90 th percentile, other definitions including >95 th or >97 th percentile or >2 standard deviations above the median, or a birth weight of >4000 or >4500 g. 13 In our study the group who had an EFW > 95 th percentile showed the strongest association with adverse neonatal outcomes. An AC 70-75 th percentile has also been proposed as a marker of macrosomia based on reports that an AC of >75 th percentile adequately discriminated the risk for elevated amniotic fluid insulin levels from amniocentesis 27,28 and a more recent report by Chee et al 2 which suggested an AC >75 th percentile was highly predictive of LGA.…”
Section: Mean (Sd)mentioning
confidence: 55%
“…The limitations of ultrasound to detect both SGA and LGA infants are recognised. 24,25 In pregnancies without diabetes the positive predictive value of antenatal ultrasound to predict SGA Adverse outcome = one or more of the following: admission to special care nursery for >24 h, neonatal hypoglycaemia requiring treatment, jaundice requiring phototherapy, respiratory distress syndrome, shoulder dystocia, PH < 7.15, or five minute Apgar score < 5. ‡…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort study, in which 32-week-old ultrasound scans of 521 diabetic pregnant women were analyzed, the authors found that EFW had a reasonable sensibility (80.3%) and a high negative predictive value (96%), but a low positive predictive value (38%) in LGA detection. 27 In addition to weight extremes, late gestational ages and obesity itself can reduce the accuracy of ultrasound results in diabetic pregnant women compared with low-risk pregnant women. 27 However, as it is a calculated indirect measurement, the EFW has an estimated margin of error of 10 to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition to weight extremes, late gestational ages and obesity itself can reduce the accuracy of ultrasound results in diabetic pregnant women compared with low-risk pregnant women. 27 However, as it is a calculated indirect measurement, the EFW has an estimated margin of error of 10 to 15%. 28 Thus, all these factors point us to look differently to the measurements of this population.…”
Section: Discussionmentioning
confidence: 99%